Secular devotion : Afro-Latin music and imperial jazz - Brennan, Timothy (Verso, 2008)
Popular music in the Americas, from jazz, Cuban Latin and salsa to disco and rap, is overwhelmingly neo-African. Created in the midst of war and military invasion, and filtered through a largely European outlook, these musical forms are completely modern in their sensibilities: they are in fact the very sounds of modern life. But the African religious philosophy at their core involved a longing for earlier eras - ones that pre-dated the technological discipline of labor forced on captive populations by the European occupiers. In this groundbreaking new book, Timothy Brennan shows how the popular music of the Americas - the music of entertainment, nightlife, and leisure - is an act of devotion to an African religious worldview that survived the ravages of slavery and found its way into the rituals of everyday listening. In doing so he explores the challenge posed by Afro-Latin music to a world music system dominated by a few wealthy countries and the processes by which Afro-Latin music has been absorbed into the imperial imagination.